A quick guide to behaviour management in the early years - Bullock, Emily (Emily E.).; Brownhill, Simon (Los Angeles : SAGE, 2011)
Managing the behaviour of young children can be a real challenge. This book provides you with 100 tried and tested ideas for long, medium and short term. It shows how to select and adopt the right approach, how to analyze, reflect on and modify practice and how to ensure consistency and fairness so that positive behaviour develops.--[book cover].
Includes bibliographical references (p. [122]) and index.
Keywords: Classroom management; Early childhood education; Behavior modification